Analysis of behavioral finance on trading strategy: Empirical study on stock market index return using Lunar Phase - Tjandra, Eric (2017)
This paper conducts a study of behavioral finance by relating human’s mood and lunar phases. Starting with the discussion of Efficient Market Hypothesis, its critics and flawed arguments, into the psychology that affected investor behavior as known as behavioral finance. More specifically, recent studies have connected lunar phases to the individual moods and the stock market returns. The finding results indicate that the days around full moon have a relatively lower return compared to the days around the new moon, which the results have shown from the study of 22 countries from 1999 to 2017. Using pooled regression with PCSE, the fluctuation of the return difference found to be around 6 bps on the average. However, extensive evidence shows that the magnitude return is not caused by those two popular lunar phases. Instead, third quarter lunar phases show the difference is much higher and shows a significant result.